The association between blood glucose level and cognitive dysfunction among acute traumatic brain injury in Manado, Indonesia - Sekeon, Sekplin A. S.; Kembuan, Mieke A. H. N. (International Journal of Research in Medical Sciences, 2018)
Background: Traumatic brain injury (TBI) is a public health challenge. TBI contributes to chronic physical impairment and also disrupt mental and personality aspects. Cognitive dysfunction is influenced by multiple factors, including blood glucose level. The objective of the study was to analyze the association between blood glucose level and cognitive dysfunction among TBI patients. Methods: A hospital-based observational study was conducted with cross-sectional design for six months period. Population of research were all of TBI patients treated at the emergency unit. Eligible sample were obtained with total sampling technique. Dyslgycemia was defined as random blood glucose level outside the range of 80-200mg/dl; cognitive dysfunction was defined as MMSE score <26. Statistical analysis with SPSS version 17.0 was employed. Chi square test and odd ratio were executed, p value <0,05 were regarded as significant level. Results: Majority of the 124 patients was male (75.8%), in 21-30 age group (20.7%), mostly due to RTA, specifically from motorcycle-related accident. Most of the motorcyclist (56,5%) were not using helmet. Unconsciousness was in 65.8% sample. Seizure was found in 3.9% of total patients; almost half of patients had history of headache (40.8%). Vomit was found in 30.3% of patients. Vertigo or dizziness post-trauma was in 3.9% patients; almost one third of patients had history of alcohol consumption (30.3%). Majority (65.8%) were in GCS 13-15. Proportion of dysglycemia and cognitive dysfunction were 4.8% and 14.5% consecutively. Odd ratio analysis revealed that dysglycemic group have 3 times higher risk to develop cognitive dysfunction, but the association was statistically not significant. Conclusions: The association between random blood glucose level and cognitive dysfunction among acute traumatic brain injury was statistically not significant.